Implementation of a program for type 2 diabetes based on the Chronic Care Model in a hospital-centered health care system: "the Belgian experience" - Van Royen Paul; Vermeire Etienne; Wens Johan; Nobels Frank; Snauwaert Boris; Feyen Luc; Bastiaens Hilde; Sunaert Patricia; De Maeseneer Jan; De Sutter An; Willems Sara (BMC, 2009)
Abstract Background Most research publications on Chronic Care Model (CCM) implementation originate from organizations or countries with a well-structured primary health care system. Information about efforts made in countries with a less well-organized primary health care system is scarce. In 2003, the Belgian National Institute for Health and Disability Insurance commissioned a pilot study to explore how care for type 2 diabetes patients could be organized in a more efficient way in the Belgian healthcare setting, a setting where the organisational framework for chronic care is mainly hospital-centered. Methods Process evaluation of an action research project (2003-2007) guided by the CCM in a well-defined geographical area with 76,826 inhabitants and an estimated number of 2,300 type 2 diabetes patients. In consultation with the region a program for type 2 diabetes patients was developed. The degree of implementation of the CCM in the region was assessed using the Assessment of Chronic Illness Care survey (ACIC). A multimethod approach was used to evaluate the implementation process. The resulting data were triangulated in order to identify the main facilitators and barriers encountered during the implementation process. Results The overall ACIC score improved from 1.45 (limited support) at the start of the study to 5.5 (basic support) at the end of the study. The establishment of a local steering group and the appointment of a program manager were crucial steps in strengthening primary care. The willingness of a group of well-trained and motivated care providers to invest in quality improvement was an important facilitator. Important barriers were the complexity of the intervention, the lack of quality data, inadequate information technology support, the lack of commitment procedures and the uncertainty about sustainable funding. Conclusion Guided by the CCM, this study highlights the opportunities and the bottlenecks for adapting chronic care delivery in a primary care system with limited structure. The study succeeded in achieving a considerable improvement of the overall support for diabetes patients but further improvement requires a shift towards system thinking among policy makers. Currently primary care providers lack the opportunities to take up full responsibility for chronic care. Trial registration number ClinicalTrials.gov Identifier: NCT00824499